Electricity generation and the environment - Breeze, Paul (Power generation series., 2017)
This book is a guide to the evolution of environmental awareness, what that environmental awareness has taught the industry, and how technologies can be used to test and improve power performance. It explores various life-cycle assessments, renewable and alternative power sources such as hydropower and transportation, external impacts on the decisions to implement systems and technologies, and the economic and environmental viability of each power generation system covered.